Profiling of Sensory Attributes Shrimp Crackers from East Java Using The Rate-All-That-Apply Method - Ahmad Wahfi Nuris Eko Prasojo; Sri Winarti (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Shrimp crackers are a traditional food that is quite popular among the public. The ingredients used in making shrimp crackers include tapioca flour, shrimp, eggs, sugar, salt, and garlic. The composition and proportion of the raw materials used in shrimp crackers can affect the sensory profile characteristics of the resulting shrimp crackers. This study aims to determine the sensory profile of shrimp crackers and consumer preferences for shrimp crackers from five producers with varying proportions of shrimp and tapioca flour. The sensory profile of shrimp crackers was determined using the Rate-All-That-Apply (RATA) method, which produced 12 sensory attributes, namely seafood aroma, fatty aroma, white color, golden brown color, crunchy texture, dense texture, shrimp flavor, savory flavor, salty flavor, sweet flavor, gritty mouthfeel, and throat irritation mouthfeel. The best sample, based on consumer preference, was sample 964DM, with dominant sensory attributes including seafood aroma, shrimp flavour, savoury flavour, sweet flavour, salty flavour, and dense texture. In sample 964DM, the percentage of shrimp used was the highest among the other samples, at 25%. The panellists' preference results show that sample 964DM is preferred by 80-100% of the panellists. Contribution to Sustainable Development Goals (SDGs):SDG 2 : Zero HungerSDG 9 : Industry, Innovation, and InfrastructureSDG 12 : Responsible Consumption and Production